High Voltage LiCoO2 Cathodes with High Purity Lithium Bis(oxalate) Borate (LiBOB) for Lithium-Ion Batteries - Subas, Yaprak; Afyon, Semih (Amer Chemical Soc, 2022)
Lithium bis(oxalate) borate, LiB(C2O4)(2) (LiBOB) can be used as an electrolyte additive for lithium-ion batteries (LIBs) to prevent structural change and electrolyte decomposition by developing a protective solid electrolyte interphase (SEI) on the cathode surface. However, impurities present in LiBOB result in significant electrochemical performance decays related to higher full cell impedance. Here, a practical purification technique is performed to remove these impurities within the as-synthesized anhydrous LiBOB in which we further add 1 wt % in 1 M LiPF6 in EC:DMC (1:1) electrolytes to achieve a more stable cycling performance for high voltage applications of LiCoO2 (LCO) cathodes. The phase and purity of as-synthesized LiBOB and recrystallized LiBOB is determined by a combination of X-ray powder diffraction (XRPD), Fourier-transform infrared (FTIR) spectra, and scanning electron microscopy (SEM) measurements. The LIB performance with the addition of high purity LiBOB as an electrolyte additive is investigated via galvanostatic charge-discharge cycling, rate capability, and cyclic voltammetry (CV) measurements within a voltage range of 3.0-4.4 V. The cell containing 1 wt % recrystallized LiBOB shows superior cycling performance, rate capability with higher energy density, and Coulombic efficiency in comparison with the reference cell through the formation of a passivation layer on the LCO surface. Thus, for the LiBOB added cell, the crystal structure of LiCoO2 is well-maintained even at higher potentials after 100 cycles according to the ex situ XRPD and SEM analyses. Therefore, high-purity LiBOB improves the interfacial stability of the LCO cathode by inhibiting oxidative decomposition of electrolytes, undesirable structural changes, and cobalt dissolution bringing about safer cycling even at high operation voltages.
Keywords: LiBOB; electrolyte additive; solid electrolyte interface; LiCoO2; high voltage